Implementasi Nilai-Nilai Kepedulian Lingkungan Hidup Dalam Mata Pelajaran Pendidikan Agam Islam - Zaky Fajar Taufiqurrahman; Muthi’ah Hijriyah (Universitas Ahmad Dahlan, 2019)
Environmental care behavior can change the environment that is initially dry to be beautiful full of lush plants that thrive and a sense of comfort for schools and school residents. While these subjects have four pillars, namely: Fiqh, Ski, Al-Qur'an Hadist, and Akidah Akhlaq, which are muttering to each other. The school has also successfully integrated formal lessons with environmental education materials. From the description above, the authors formulated the focus of the study as follows: How the values of caring, implementation, inhibiting and supporting factors in the process of growing values of environmental concern in middle school. A. Wahid Hasyim. The research uses a case study qualitative research. Data collection techniques using observation, interviews, and documentation. For data analysis techniques using: data reduction, data display, data verification. To check the validity of the data by: (1) credibility: a. extension of participation, b. perseverance of observation, c. triangulation, d. Negative Case Analysis, e. Using reference material, f. using member check, (2) transferability, (3) dependability, (4) confirmation. The results showed that: The value of environmental care in AWH Middle School was applied both in theory and practice, while for constraints was financing and the formation of new personalities, for supporters in this case the participation of all school members in maintaining cleanliness.